2019
DOI: 10.1007/978-981-13-9913-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Astroglia in Alzheimer’s Disease

Abstract: Alzheimer's disease is the most common cause of dementia. Cellular changes in the brains of the patients suffering from Alzheimer's disease occur well in advance of the clinical symptoms. At the cellular level, the most dramatic is a demise of neurones. As astroglial cells carry out homeostatic functions of the brain, it is certain that these cells are at least in part a cause of Alzheimer's disease. Historically, Alois Alzheimer himself has recognised this at the dawn of the disease description. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 338 publications
1
47
0
Order By: Relevance
“…Indeed, astrocytic dysfunction has been implicated in AD pathogenesis. [336][337][338] Iron accumulation also occurs in microglia in the vicinity of Ab plaques in mice, a finding that is consistent with the finding of iron accumulation in the vicinity of plaques in the brains of patients. 339,340 Experiments in AD mice have found that although promoting neuroinflammation, microglia have a reduced ability to phagocytose Ab, thus potentiating damage to the brain.…”
Section: Age-associated Neurodegenerative Diseasessupporting
confidence: 88%
“…Indeed, astrocytic dysfunction has been implicated in AD pathogenesis. [336][337][338] Iron accumulation also occurs in microglia in the vicinity of Ab plaques in mice, a finding that is consistent with the finding of iron accumulation in the vicinity of plaques in the brains of patients. 339,340 Experiments in AD mice have found that although promoting neuroinflammation, microglia have a reduced ability to phagocytose Ab, thus potentiating damage to the brain.…”
Section: Age-associated Neurodegenerative Diseasessupporting
confidence: 88%
“…In this respect, the mechanistic inquiry into AD pathogenesis and progression have recently switched from the neuron-centric doctrine to an astrocyte-centered theory [ 59 ]. Besides the evidence on the role of astrocytic K + dysregulation during AD, with the present study, we could only partially answer to this enormous issue.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Now, the NVU is a tool that can be used to understand normal brain physiology as well as the pathophysiology of numerous neurological disorders. [24][25][26][27][28][29] Conversely, the malfunction of astroglia in the NVU (i.e., "astrogliopathy") [30][31][32][33][34] induces neuronal dysfunction, leading to various neurological disorders including cerebrovascular disease (e.g., stroke and small vessel disease-like Binswanger's disease and cerebral autosomaldominant arteriopathy with subcortical infarct and leukoencephalopathy [CADASIL]/ 35 cerebral autosomal recessive arteriopathy with subcortical infarct and leukoencephalopathy [CARASIL]), 36,37 neurodegenerative disease (e.g., Alzheimer's disease, 38,39 Parkinson's disease, 40,41 and amyotrophic lateral sclerosis [ALS]), [42][43][44] and neuroimmunological disease (e.g., multiple sclerosis [MS], [45][46][47][48] and neuromyelitis optica spectrum disorder [NMOSD]). 49,50 This review will focus on the supportive roles of astroglia in the NVU from the perspective of three major metabolic compartments with neurons: (i) glucose and lactate; (ii) fatty acid and ketone bodies (KBs); and (iii) D-and L-serine.…”
Section: Introductionmentioning
confidence: 99%